2008
DOI: 10.1080/09537100701777329
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D in human platelets: Presence of isoenzymes and participation of autocrine stimulation during thrombin activation

Abstract: Phospholipase D (PLD), which hydrolyzes phosphatidylcholine to phosphatidic acid (PA) and choline, is present in human platelets. Thrombin and other agonists have been shown to activate PLD but the precise mechanisms of activation and PLDs role in platelet activation remains unclear. We measured thrombin-stimulated PLD activity in platelets as formation of phosphatidylethanol. Since no specific PLD inhibitors exist, we investigated possible roles for PLD in platelets by correlating PLD activity with platelet r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 77 publications
5
34
1
Order By: Relevance
“…This is in accordance with experiments performed by Vorland and Holmsen who found no effect on lysosomal secretion when using the specific TXA2 inhibitor SQ 29.548 in thrombin-stimulated platelets [27] and Chronos et al who compared the exposure of CD63 and P-selectin in healthy subjects before and after ingestion of ASA [31]. McKenzie et al reported that the spontaneous expression of LAMP-1, LIMP and P-selectin was reduced in platelets treated with ASA in vitro [32].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is in accordance with experiments performed by Vorland and Holmsen who found no effect on lysosomal secretion when using the specific TXA2 inhibitor SQ 29.548 in thrombin-stimulated platelets [27] and Chronos et al who compared the exposure of CD63 and P-selectin in healthy subjects before and after ingestion of ASA [31]. McKenzie et al reported that the spontaneous expression of LAMP-1, LIMP and P-selectin was reduced in platelets treated with ASA in vitro [32].…”
Section: Discussionsupporting
confidence: 75%
“…A reduction in NAG release has previously been found upon pre-incubation of platelets with the ADP-removing system, creatine phosphate/creatine phosphokinase [27]. Moreover, we observed that thrombin-induced aggregation was not reduced by cangrelor.…”
Section: Discussionsupporting
confidence: 64%
“…While PLD1 has a low basal activity and is readily activated by PKC and small GTPases of the adenosine diphosphate 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Elvers et al PLD as negative regulator of platelets 5 marginally induced by a variety of activators. In platelets, both PLD isoforms are present [23].…”
Section: Introductionmentioning
confidence: 99%
“…8,10 In platelets, both PLD isoforms are present and become activated upon stimulation with various agonists. 9,11 Recently, we demonstrated that PLD1 contributes to GPIb-dependent platelet integrin activation, whereas absence of both PLD isoforms leads to a defect in α-granule release in addition to the defects observed in PLD1-deficient platelets. 12 Moreover, Pld1 −/− /Pld2 −/− mice are protected from arterial thrombosis and ischemic stroke but do not exhibit hemostatic defects.…”
mentioning
confidence: 99%
“…The 2 mammalian PLD isoforms, PLD1 and PLD2, are widely expressed and are 50% identical in amino acid sequence. 8,9 PLD1 and PLD2 locate to distinct intracellular membrane compartments and have been implicated in many important signaling pathways and cell biological processes. 8,10 In platelets, both PLD isoforms are present and become activated upon stimulation with various agonists.…”
mentioning
confidence: 99%